Spatiotemporal Distribution and Host–Vector Dynamics of Japanese Encephalitis Virus - Qikai Yin; Bin Li; Ruichen Wang; Kai Nie; Shihong Fu; Songtao Xu; Fan Li; Qianqian Cui; Dan Liu; Huanyu Wang; Guodong Liang (Viruses)
Japanese encephalitis (JE), a mosquito-borne viral disease caused by the Japanese encephalitis virus (JEV), remains a significant public health threat in Asia. Although vaccination programs have successfully reduced the incidence of JE, challenges persist in the adult population, and the emergence of rare JEV genotypes poses additional risks. In this study, a phylogenetic analysis of the whole JEV genome sequence, along with a temporal–spatial analysis of isolates and a host–vector analysis, was used to examine the changes in JEV transmission dynamics before and after 2012. The results revealed persistent differences between the dominant G1 and G3 genotypes, as well as the re-emergence of G4 and G5 genotypes. Although JEV has been detected in non-traditional vectors and atypical mammalian hosts, Culex tritaeniorhynchus and pigs remain the primary vector and amplifying host, respectively. These findings underscore the need to enhance existing JEV genotype surveillance while addressing emerging threats from genotype diversity, host expansion, and geographic spread.